2018
DOI: 10.1002/ceat.201800133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steam Addition during Calcination on Carbonation Behavior in a Calcination/Carbonation Loop

Abstract: The effects of steam addition during calcination on the carbonation behavior of calcium‐based sorbents in cyclic calcination/carbonation experiments were investigated. Variations in the CaO conversion rate during carbonation were measured to evaluate the influence of operating conditions and particle size on the carbonation reaction in kinetic‐ and diffusion‐controlled reaction regimes. Surface sintering and particle aggregation during cyclic calcination/carbonation affected the sorbent surface area, pore volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Both the sorbent surface area and pore volume were significantly increased when steam was added during carbonation. The increased sorbent pore volume was effective in retarding carbonation into the diffusion-controlled reaction regime [21]. Siriruang et al [38] and Liu et al [39] reported that the enhanced reactivity of CaO by steam during carbonation was mainly ascribed to the formation of Ca(OH) 2 , as the reactivity of Ca(OH) 2 is much higher than CaO.…”
Section: Effect Of Steam Addition During Carbonationmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the sorbent surface area and pore volume were significantly increased when steam was added during carbonation. The increased sorbent pore volume was effective in retarding carbonation into the diffusion-controlled reaction regime [21]. Siriruang et al [38] and Liu et al [39] reported that the enhanced reactivity of CaO by steam during carbonation was mainly ascribed to the formation of Ca(OH) 2 , as the reactivity of Ca(OH) 2 is much higher than CaO.…”
Section: Effect Of Steam Addition During Carbonationmentioning
confidence: 99%
“…Donat et al [8] showed that steam injection during calcination enhanced CO 2 capture at concentration up to 1% with no significant improvement thereafter. However Chou et al [21] found that a higher steam concentration up to 80 % continued to enhance the sorbent reactivity. The increased capture capacity was due to a shift from smaller to large pores, possibly eliminating the trigger time retard in the fast-kinetic stage and increasing carbonation rate in the diffusion regime.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The enhancement during carbonation becomes apparent in the diffusioncontrolled regime [230]- [232] and is usually not noticeable in the fast, kinetically-controlled regime. Remarkably, only small amounts of steam present during carbonation, < 1 vol.%, are sufficient to improve the rate of conversion significantly [193], [205], [212]. Furthermore, the driving force (pCO2 -pCO2,eq) needed for carbonation to commence is lowered substantially in the presence of steam, suggesting that steam potentially affects the reaction pathway for carbonation [193].…”
Section: Effect Of Steam On Caomentioning
confidence: 99%
“…Researchers also estimate a further rise of cement industry in the world, while the main focus is on specific countries, like China and India, together with areas from the Middle East and Northern Africa . Lately, a number of improvements were suggested for the cement industry with the aim to reduce CO 2 emissions in the atmosphere , such as the use of alternative fuels, increasing the process energy efficiency by implementing the oxy‐fuel combustion technology , , and adding post‐combustion system units for capturing CO 2 .…”
Section: Introductionmentioning
confidence: 99%